2007
DOI: 10.1074/jbc.m610316200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix-regulated Gene Expression Requires Cooperation of SWI/SNF and Transcription Factors

Abstract: Extracellular cues play crucial roles in the transcriptional regulation of tissue-specific genes, but whether and how these signals lead to chromatin remodeling is not understood and subject to debate. Using chromatin immunoprecipitation assays and mammary-specific genes as models, we show here that extracellular matrix molecules and prolactin cooperate to induce histone acetylation and binding of transcription factors and the SWI/SNF complex to the ␤-and ␥-casein promoters. Introduction of a dominant negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 58 publications
6
87
0
1
Order By: Relevance
“…There is evidence suggesting that the ECM maintains a high level of histone H4 acetylation upstream of the αs1-casein gene, especially at the level of a distal prolactin and ECM-sensitive enhancer region (Jolivet et al 2005). Recently, Xu et al determined that extracellular matrix molecules cooperate with prolactin to induce histone acetylation and the binding of transcription factors as well as the ATP-dependent SWI chromatin remodeling complex to the β-casein promoter (Xu et al 2007).…”
Section: Adhesion Signaling In Mammary Epithelial Cell Differentiatiomentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence suggesting that the ECM maintains a high level of histone H4 acetylation upstream of the αs1-casein gene, especially at the level of a distal prolactin and ECM-sensitive enhancer region (Jolivet et al 2005). Recently, Xu et al determined that extracellular matrix molecules cooperate with prolactin to induce histone acetylation and the binding of transcription factors as well as the ATP-dependent SWI chromatin remodeling complex to the β-casein promoter (Xu et al 2007).…”
Section: Adhesion Signaling In Mammary Epithelial Cell Differentiatiomentioning
confidence: 99%
“…The diagram includes the pathways known to be affected by CTGF/ CCN2 during lactogenic differentiation of mammary epithelial cells in primary cells or established cell lines process. Lactogenic differentiation may also depend on expression and stabilization of CTGF/CCN2 -integrin complexes that promote prolactin-induced Stat5 activity (Xu et al 2007(Xu et al , 2009.…”
Section: Ccn2 Protein Contributes To Lactogenesismentioning
confidence: 99%
“…BRG1 has been shown to direct different cellular processes by recruitment to cis elements through divergent transcription factors including hormone receptors, the erythroid factors erythroid Krüppel-like factor and GATA-1 (which activate the ␤-globin gene) and C/EBP␤ (16,17,42,43). Similar to our findings related to the regulation of Cyp24a1 transcription, C/EBP␤ has been reported to recruit and cooperate with BRG1 to regulate the expression of myeloid genes (15), the osteocalcin gene in osteoblastic cells (16), and the mammary tissue-specific ␤-and ␥-casein genes (17).…”
Section: Discussionmentioning
confidence: 99%
“…In additional studies in COS-7 cells, suboptimal 1,25(OH) 2 Previous studies from our laboratory showed that C/EBP␤ is induced by 1,25(OH) 2 D 3 in kidney and osteoblastic cells and is a potent enhancer of VDR-mediated Cyp24a1 transcription (26). C/EBP␤ has also been reported to recruit the SWI/SNF complex to regulate cell type-specific genes (15)(16)(17). Hence, we next investigated the role of BRG1 in the C/EBP␤ enhancement of 1,25(OH) 2 D 3 -induced Cyp24a1 transcription.…”
Section: Brg1-containing Swi/snf Complex Vdr and C/ebp␤ Cooperate Imentioning
confidence: 94%
See 1 more Smart Citation